2006
DOI: 10.1021/jm060539t
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Imidazoline Derivatives as Potent and Selective Adenosine A1 Receptor Antagonists

Abstract: Novel tricyclic imidazoline antagonists of the adenosine A1 receptor are described. For key compounds, the selectivity level over other adenosine receptor subtypes is examined along with their in vivo effects in a rat diuresis model. Compound 14, the (R)-isomer of 7,8-dihydro-8-ethyl-2-(4-bicyclo[2.2.2]octan-1-ol)-4-propyl-1H-imidazo[2,1-i]purin-5(4H)-one, is a particularly potent adenosine A1 receptor antagonist with good selectivity over the other three adenosine receptor subtypes: A1 (human) Ki=22 nM; A2A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…6 and table 6). Cycloalkyl-substituted dihydro-imidazo[2,1- i ]purinones ( 127 , 128 ) showed high A 1 affinity and selectivity combined with improved water-solubility due to the presence of a basic nitrogen atom that can be protonated (Suzuki et al 1992; Vu et al 2006). A new class of heterotricyclic xanthine derivatives in which the 3-alkyl-substituent is tethered to the N9 atom – pyrimido[1,2,3- cd ]purinediones ( 151–153 ) - was synthesized and investigated (fig.…”
Section: Adenosine A1 Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and table 6). Cycloalkyl-substituted dihydro-imidazo[2,1- i ]purinones ( 127 , 128 ) showed high A 1 affinity and selectivity combined with improved water-solubility due to the presence of a basic nitrogen atom that can be protonated (Suzuki et al 1992; Vu et al 2006). A new class of heterotricyclic xanthine derivatives in which the 3-alkyl-substituent is tethered to the N9 atom – pyrimido[1,2,3- cd ]purinediones ( 151–153 ) - was synthesized and investigated (fig.…”
Section: Adenosine A1 Receptor Antagonistsmentioning
confidence: 99%
“… a h = human; m = mouse; r = rat; a few A 2B data may be from functional (cAMP) studies; nd = no data available 1 Suzuki et al, 1992b 2 Vu et al, 2006 3 Ozola et al, 2003 4 Müller et al, 2002a 5 Müller et al, 2002b 6 Saki et al, 2002 7 Geis et al 1995 8 Drabczynska et al, 2004 9 Drabczynska et al, 2006 10 Drabczynska et al, 2007a 11 Drabczynska et al, 2007b 12 Priego et al, 2002 13 Priego et al, 2008 14 Baraldi et al, 2005 15 Pastorin et al, 2005 16 Weyler et al, 2006 17 Müller, 1994 …”
Section: Figmentioning
confidence: 99%
“…However, the poor pharmaceutical properties of this molecule (low aqueous solubility and a tendency to rearrange to inactive products in both acidic and basic media) led Kiesman et al (Kiesman et al 2006a, b) to design more pharmaceutically acceptable antagonists by exploring the placement of polar substituents on linearly substituted 8-cycloalkyl 1,3-dipropylxanthines. For structurally related imidazolines, see Vu et al (2006). The binding affinities of selected 8-cyclohexyl and 8-bicyclo[2.2.2]octyl xanthines are listed in Table 5.…”
Section: Bg9928mentioning
confidence: 99%
“…The potency and efficacy in renal protection of tonapofylline have been demonstrated both in vitro and in vivo in rodent and primate models. [6][7][8][9][10][11] The renal effects of tonapofylline have been investigated in patients with heart failure (HF). 12 In 50 HF patients, Greenberg and colleagues 12 found that oral tonapofylline was associated with increased urinary sodium excretion, increased urine volume, and reduction in body weight, suggesting that tonapofylline may facilitate resolution of congestion in HF patients in conjunction with standard background loop diuretics.…”
mentioning
confidence: 99%